Clinical Profile Examination of Glucose, Uric Acid, and Cholesterol in Residents of Jatimulyo Village, Jember - Philips Carel Perdana; Winitasha Alya Islami; Rizqy Aiddha Yuniawati; Nabilla Feirizky Chairunnisa; Qonita Pitra Larasati; Ali Akbar Haryanto; Adinda Fitria Nur Izzati; Renza Salwa Chintya; Syifa Kamila; Syeila Rahmadina; Aulia Rahman (Jurnal Pengabdian Masyarakat Bestari, 2022)
Jember Regency is the area with the third highest population density in East Java Province, so the random blood sugar, uric acid, blood pressure, and cholesterol data obtained are able to reflect the real picture of Indonesian public health, especially in Jatimulyo Village. This study uses a prospective descriptive study, information about the patient's blood sugar, uric acid, and cholesterol profile is taken directly through a physical examination. The total data obtained from the health checks of Jatimulyo residents amounted to 26 residents. The results of the Jatimulyo residents' health checks which included blood sugar, uric acid, and cholesterol were mostly normal, while blood pressure was mostly found in the prehypertension categor